2016
DOI: 10.15171/ijb.1309
|View full text |Cite
|
Sign up to set email alerts
|

Green Nanoparticles Engineering on Root-knot Nematode Infecting Eggplants and Their Effect on Plant DNA Modification

Abstract: Background Root-knot nematodes are known to cause significant damage to eggplants. New approaches by green silver nanoparticles (GSN) are used to control plant-parasitic nematode to avoid chemical nematicide hazards. Objectives Analyses of the incorporation of different concentrations of nanoparticles on two different algae (Ulva lactuca and Turbinaria turbinata) were carried out. Furethermore, the effect of GSN on the eggplant DNA profile was studied using RAPD and EST molecular markers. Materials and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(29 citation statements)
references
References 20 publications
3
20
0
Order By: Relevance
“…The biostimulant effect by both ACE and cyanobacteriumbased Ag-NPs on faba bean growth parameters is possibly due to micronutrients and many organic compounds such as auxins, gibberellins, and precursor of ethylene and betaine produced by algal cells [56]. In this context, green synthesized Ag-NPs had no plant phototoxicity when they were used to control the nematodal infection by M. javanica [57]. Further investigations are still needed to separate and purify of cyanobacterium-based Ag-NPs from the suspension mixture with AgNO 3 .…”
Section: Bio-stimulant Effect Of Cyanobacterium-based Ag-nps On Faba mentioning
confidence: 99%
“…The biostimulant effect by both ACE and cyanobacteriumbased Ag-NPs on faba bean growth parameters is possibly due to micronutrients and many organic compounds such as auxins, gibberellins, and precursor of ethylene and betaine produced by algal cells [56]. In this context, green synthesized Ag-NPs had no plant phototoxicity when they were used to control the nematodal infection by M. javanica [57]. Further investigations are still needed to separate and purify of cyanobacterium-based Ag-NPs from the suspension mixture with AgNO 3 .…”
Section: Bio-stimulant Effect Of Cyanobacterium-based Ag-nps On Faba mentioning
confidence: 99%
“…Silver ion (Ag + ) and its compounds are highly toxic to microorganisms, exhibiting strong biocidal effects on many species of bacteria and fungi ( Park et al, 2006 ; Kim et al, 2007 ; Lara et al, 2011 ). Recently, Ag nanoparticles (AgNP) have shown evidence of being a potentially effective nematicide ( Cromwell et al, 2014 ; Abdellatif et al, 2016 ; Hassan et al, 2016 ; Nassar, 2016 ; Taha, 2016 ).…”
mentioning
confidence: 99%
“…The first report on the bio-efficacy of AgNP on a plant-parasitic nematode was provided by Cromwell et al (2014) against root-knot nematode on bermuda grass with mixed results, the lab assays revealed promising results but field experiments were not conclusive. Subsequent studies have explicitly revealed promising results of AgNP ( Abdellatif et al, 2016 ; Hassan et al, 2016 ) and FeNP ( Sharma et al, 2017 ) against Meloidogyne incognita on eggplant, tomato, and okra. The results were similar to fenamiphos and oxamyl at 0.003 ml/kg soil ( Hassan et al, 2016 ).…”
mentioning
confidence: 99%
“…They have found significantly effect on EPNs reproductivity at two concentration 500 and 1000 ppm. Abdellatif et al, 2016 reported effective control of root Knot nematodes T. turbinate and U. lactuca similar to chemical control in eggplant.…”
Section: Discussionmentioning
confidence: 91%
“…Ardakani et al, 2016 studied effectiveness of AgNPs on M. incognita in case of tomato plants, dose of 800,400 and 200 mg/ml-1 of AgNP were highly significant to immobility and to mortality of J2 M. incognita and Ti02 nanoparticles showed 4.3 percent and 2 percent mortality when applied 800 and 400 mg/ ml-1 concentration. Abdellatif et al, 2016 studied the influence of silver nanoparticles on M. javanica reproduction and growth. They have observed that AgNPs treatment was equally effective as chemical treatment (Vydate 24%L), resulted in a reduction of egg-masses number per root system.…”
Section: Discussionmentioning
confidence: 99%